Sustainable bioenergy production - Wang, Lijun, 1971 March 20- (CRC Press, Taylor and Francis, 2014)
Given the environmental concerns and declining availability of fossil fuels, as well as the growing population worldwide, it is essential to move toward a sustainable bioenergy-based economy. However, it is also imperative to address sustainability in the bioenergy industry in order to avoid depleting necessary biomass resources. Sustainable Bioenergy Production provides comprehensive knowledge and skills for the analysis and design of sustainable biomass production, bioenergy processing, and biorefinery systems for professionals in the bioenergy field. Focusing on topics vita.
Keywords: Biomass energy.; elektronické knihy; electronic books